UJI PENGARUH PESTISIDA NABATI MENGGUNAKAN EKSTRAK DAUN MIMBA (Azadirachta indica) DAN UMBI GADUNG (Dioscorea hispida Dennst.) TERHADAP WALANG SANGIT PADA TANAMAN PADI - Ilmah Noor; Sasi Gendro Sari; Faulina Faulina (Universitas Lambung Mangkurat, 2023)
Vegetable pesticides are pesticides whose basic ingredients come from plants. The plants that can be used as vegetable pesticides are neem (Azadirachte indica) and Gadung (Dioscorea hispida Dennst.) plants which contain active ingredients that can control insect pests. Neem leaves contain active ingredients in the form of azadirachtin, meliantriol, salanin, and nimbin. Meanwhile, gadung tubers are known to contain toxic active compounds, namely dioscorin, diosgenin, dioscin, saponins, alkaloids, and phenols. The purpose of this study was to determine the effectiveness of the effect of botanical pesticides using extracts of neem leaves and Gadung tubers against rice pests, namely Walang Sangit (Leptocorisa oratorius F.). The method of application to Walang Sangit was carried out with different concentrations, namely 40 ml/L, 60 ml/L, and 80 ml/L. The time of application of the extract was carried out in 3 treatments, namely in the morning (08.00 – 10.00 WITA), in the afternoon (11.00 – 12.00 WITA), and in the afternoon (16.00 – 18.00 WITA). The test results were seen 24 hours after the application of the extract. The results showed that the concentration that had the best results was at a concentration of 40 ml/liter which was able to kill or kill stink bugs with a period of 48-50 hours. This can be used as an alternative or one of the recommendations in controlling insect pests, especially for walang sangit.